Észak-Afrika és a Földközi-tenger térségének geopolitikai kihívásai, különös tekintettel a mezőgazdaságra és az élelmezés-biztonságra - Somogyi, Norbert (Afrika Tanulmányok / Hungarian Journal of African Studies, 2020)
Most climate change models clearly indicate that the process will have more serious effects than average in North Africa, particularly on agricultural production. In parallel, current demographic trends show that population growth in Africa, including the Northern African region is continuous and dynamic, which requires more food, especially basic foodstuff, however, despite the fact that the continent has significant agricultural potential, it is not self-sufficient in food. The stake is high, as dependence on foodimport has to be at least stabilised or reduced if it is possible, in this region where the population is rapidly growing and climate change has several negative impacts. However, geopolitical stability of the region is essential not only for Mediterranean, but also for the whole European continent. Due to the effects of complex crises (such as economic, environmental and ecological), the development of proper international development policy strategies is ever more prevalent, in order to recover the economy of countries mostly affected by the migration threat, to create jobs and to reduce young people’s willingness to migrate. As agriculture has a vital role in this field, focusing on agricultural development programs is essential. Evidently, application of environmental friendly agriculture which can provide the protection and sustainable use of soils and water on growing areas is a key factor in this situation from an agronomic point of view. In socio-economic aspects the most important issues are eliminating conflicts which hamper sustainable soil management and ensuring generation change within farmer society. Development of infrastructure and trade routes is also necessary, furthermore, questions of water and water use, investments are important to underline. Investing in agricultural projects is initially an expensive, but recoverable solution anyway, and it is clear that development of agriculture research in these countries also serves long-term social objectives.